An analysis of production cost calculation using the full costing method in sasirangan fabric MSMEs (micro, small, and medium enterprises) in Sasirangan Village, Banjarmasin - Rukman Rukman; Endah Sri Bintari; Irma Sucidha; Ros Nirwana (Indonesia Accounting Research Journal, 2025)
This study analyzes the production cost calculation of Sasirangan fabric Micro, Small, and Medium Enterprises (MSMEs) in Sasirangan Village, Banjarmasin, using the full costing method. In the face of increasing competitive pressures, accurate cost determination is essential for MSMEs to set appropriate selling prices and maintain profitability. The research employs a qualitative approach, collecting data through interviews, observations, and documentation from a Sasirangan fabric enterprise, Kantan Sasirangan. The full costing method was applied to comprehensively account for raw materials, direct labor, and factory overhead costs. Findings reveal that labor costs constitute the largest portion of total production costs, reflecting the labor-intensive nature of traditional Sasirangan fabric production, particularly in the whipstitching process. Raw materials represent a significant share, with diverse fabric types used to target various market segments. Factory overhead costs, although smaller, support essential production and marketing activities. The calculated unit production cost is approximately Rp 79,383 per piece, providing a practical benchmark for pricing strategies that balance cultural value and market competitiveness. This research contributes to the understanding of cost management in traditional textile MSMEs and offers practical insights for similar enterprises aiming to preserve cultural authenticity while achieving economic viability.